Protest in Hitler's "National community" : popular unrest and the Nazi response - Stoltzfus, Nathan 1954- HerausgeberIn; Maier-Katkin, Birgit HerausgeberIn (Protest, culture and society, 2016)
"That Hitler's Gestapo harshly suppressed any signs of opposition inside the Third Reich is a common misperception. This book presents studies of public dissent that prove this was not always the case. It examines circumstances under which 'racial' Germans were motivated to protest, as well as the conditions determining the regime's response. Workers, women, and religious groups all convinced the Nazis to appease rather than repress 'racial' Germans. Expressions of discontent actually increased during the war, and Hitler remained willing to compromise in governing the German Volk as long as he thought the Reich could salvage victory"--Provided by publisher